Bureaucracy and burden: An Intersectionality-Based Policy Analysis of social welfare policy with consequences for carers of people with life-limiting illness. (April 2023) - Bindley, Kristin; Lewis, Joanne; Travaglia, Joanne; DiGiacomo, Michelle
Background: For informal carers of people with life-limiting illness, social welfare policy related to income support and housing has been associated with varied psychosocial issues, yet remains relatively under-explored. An intersectional approach offers potential to illuminate diverse experiences and implications. Aim: To explore the way in which caring in the context of life-limiting illness is framed within welfare policy, to articulate inequities encountered by carers, and to identify policy and practice recommendations. Design: The Intersectionality-Based Policy Analysis (IBPA) Framework was used to situate findings of a broader qualitative study. Setting/participants: Data were collected via semi-structured interviews with participants who were bereaved carers ( n  = 12), welfare workers ( n  = 14) and palliative care workers ( n  = 7), between November 2018 and April 2020, in an Australian region associated with socioeconomic disadvantage. Five elements of IBPA were applied to the products of analysis of this data. Results: Use of the IBPA Framework revealed that representations of carers and causes of their welfare needs in policy were underpinned by several assumptions; including that caring and grieving periods are temporary or brief, and that carers have adequate capacity to navigate complex systems. Policy and processes had differentiated consequences for carers, with those occupying certain social locations prone to accumulating disadvantage. Conclusions: This intersectional analysis establishes critical exploration of the framing and consequences of welfare policy for carers of people with life-limiting illness, presented in a novel conceptual model. Implications relate to intersectoral development of structural competency, responsiveness to structurally vulnerable carers in clinical practice, and needed policy changes.